2002
DOI: 10.1095/biolreprod.102.003392
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rats with 17β-Estradiol or Relaxin Rapidly Inhibits Uterine Estrogen Receptor β1 and β2 Messenger Ribonucleic Acid Levels1

Abstract: Estrogen regulates the growth and differentiation of the uterus via binding to estrogen receptors (ERs), members of the nuclear receptor family of transcription factors. Two forms of ER exist: ERalpha and ERbeta. The former is a well-characterized mediator of estrogen-induced transcription, but the function of the latter is unclear. Recent in vitro studies suggest that both splicing forms of ERbeta expressed in rat tissues, beta1 and beta2, may function as inhibitors of ERalpha transcriptional activity. To gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 64 publications
(130 reference statements)
3
18
0
Order By: Relevance
“…Observations are consistent with the fact that, in the absence of RLX, myometrial ERa expression was attenuated in RLX-null mice during late pregnancy (Siebel et al 2003). By contrast, studies in rats have shown that RLX decreased uterine ERb (ESR2) mRNA levels without affecting ERa (ESR1) mRNA levels (Pillai et al 2002). Moreover, in the cervix and vagina of RLX-null mice, chronic infusion of RLX had no effect on ERa gene expression and decreased ERb mRNA in late gestation (Parry et al 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Observations are consistent with the fact that, in the absence of RLX, myometrial ERa expression was attenuated in RLX-null mice during late pregnancy (Siebel et al 2003). By contrast, studies in rats have shown that RLX decreased uterine ERb (ESR2) mRNA levels without affecting ERa (ESR1) mRNA levels (Pillai et al 2002). Moreover, in the cervix and vagina of RLX-null mice, chronic infusion of RLX had no effect on ERa gene expression and decreased ERb mRNA in late gestation (Parry et al 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Relaxin affects expression of estrogen receptors in several tissues (Pillai et al 2002, Siebel et al 2003, Yan et al 2008, but in vitro treatment of the vas deferens with 100 ng/ml relaxin did not significantly change the levels of transcripts for the estrogen receptors Esr1, Esr2, and Gper (Fig. 6B).…”
Section: Localization Of Relaxin In the Testis And Effect Of Relaxin mentioning
confidence: 97%
“…Knowing from the reproductive system that the expression of ERs, being ligand-inducible transcriptions factors, is regulated by estrogen (Murata et al 2003;Pillai et al 2002;Xiao and Goff 1999) and that this dependency has also been proven for various brain regions (Gundlah et al 2000;Schreihofer et al 2000;Tena-Sempere et al 2004), we treated the primary hippocampal neurons with estradiol. This treatment resulted in an upregulation of ERα and a downregulation of ERβ, as immunohistochemistry and subsequent semiquantitative image analysis showed.…”
Section: Functional Roles Of Hippocampus-derived Estradiolmentioning
confidence: 99%